Caries en ortodoncia: análisis de la producción y los campos de investigación con algunos indicadores bibliométricos (2022)
The purpose of this study is to provide the professional with updated information on dental caries and how it has evolved during the years 2010-2022; To know the impact and quality of each study, provides a better understanding of the outcome of dental caries research in orthodontics. The methodology consists in providing a basic basis for a literature review with the application of some bibliometric indicators that define, analyze and verify the scientific production of caries in orthodontics for specialists, through this bibliometric consolidation is intended to contribute to prevention and treatment studies. Taking this into account, a total of 860 articles were illustrated that were included in the study for their analysis of bibliometric indicators, published in the given period. The scientific production analyzed demonstrates an interest on the part of scientists, groups and institutions to try to find prevention strategies, in addition to improving health policies.